A DARWIN C-star model grid with new dust opacities. Issue Volume 14:Issue S343(2019) (August 2018) - Eriksson, Kjell; Höfner, Susanne; Aringer, Bernhard
Abstract: We have improved the treatment of dust opacity from the small-particle limit approximation to size-dependent which leads to models with smaller grains, lower dust-to-gas ratios, but about the same mass-loss rates and outflow velocities. The K-magnitudes get brighter, whereas the V-magnitudes can be either brighter or dimmer depending on the wind properties.